1998
DOI: 10.1007/s001250050875
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular triglyceride content is increased in IDDM

Abstract: Increased lipid oxidation is related to insulin resistance [1]. Most of the fatty acids taken up by resting muscle are not oxidized directly, but enter an intramuscular pool with a slow turnover at rest and are the immediate source of lipid substrate for oxidation [2]. The NEFA taken up by muscle are incorporated to lipid droplets in muscle and 70--90 % of fatty acids entering the muscle are rapidly esterified to triglyceride (TG) [3]. For example, raising extracellular palmitate increases esterification, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 28 publications
3
29
2
Order By: Relevance
“…Thus, minimizing hyperglycemia by achieving recommended glycemic control might help to normalize the potential muscle fat abnormalities observed in type 1 diabetic subjects. However, the results from the present study and those of Ebeling et al 12 and Perseghin et al…”
Section: Diabetes Status Central and Muscle Fat Relationscontrasting
confidence: 70%
See 2 more Smart Citations
“…Thus, minimizing hyperglycemia by achieving recommended glycemic control might help to normalize the potential muscle fat abnormalities observed in type 1 diabetic subjects. However, the results from the present study and those of Ebeling et al 12 and Perseghin et al…”
Section: Diabetes Status Central and Muscle Fat Relationscontrasting
confidence: 70%
“…In the Ebeling et al 12 study, where subjects had better metabolic control (mean HbA 1c of 7.7%), no relation between muscle fat and insulin resistance was found. In the present study, no relationship was found between muscle lipids, estimated by CT scan, and HbA 1c .…”
Section: Diabetes Status Central and Muscle Fat Relationsmentioning
confidence: 87%
See 1 more Smart Citation
“…However, in single, homogeneous groups of subjects (9,(33)(34)(35) in the present study and in normoglycemic obese subjects (31), the inverse relationship between muscle triacylglycerol stores (measured by muscle biopsy, NMR, and Oil red O) and insulin sensitivity is normally not present, although exceptions exist (10,36). As for the extramyocellular triacylglycerol stores (fat and adipose cells stored outside the myofibrils but within the muscle fascia), most but not all studies (9) find no relation to insulin sensitivity (11,12,37).…”
Section: Training Insulin Sensitivity and Structural Muscle Lipidsmentioning
confidence: 99%
“…Furthermore, an inverse relationship between the amount of TG deposited in muscle and sensitivity to insulin-induced glucose uptake has been recently observed in the normal state and in various insulin-resistant conditions (14)(15)(16)(17)(18). These findings suggest that FFAs derived from skeletal muscle lipolysis may be an important endogenous energy source and indicate that increased TG deposition and enhanced lipolysis and FFA mobilization/oxidation in skeletal muscle are important in the pathogenesis of peripheral insulin resistance via interactions between glucose and FFA utilization in muscle cells.…”
mentioning
confidence: 98%